Child hostages - Incidence and outcome - Butler, William M. (Journal of interpersonal violence, 1995)
This study reports on how often children are held hostage and the likelihood of their being physically harmed by the hostage taker. Forty percent of the negotiated hostage incidents reported by law enforcement agencies participating in the study involved child hostages. One percent of these negotiated incidents resulted in serious physical injury to a child hostage and 1% resulted in the death of a child hostage. In 85% of the negotiated hostage incidents involving a child hostage, the perpetrator was a relative. These results point to the need for mental health and law enforcement personnel who work in hostage situations to be trained to deal with situations involving child hostages